Sustainable development in rural China : farmer innovation and self-organisation in marginal areas - Wu, Bin, 1957 November 6- (RoutledgeCurzon, 2003)
Sustainable development in marginal areas, especially in those where rural poverty and environmental degradation are interwoven, is a great concern of development agencies worldwide, and much effort is put into development programmes, technology transfer schemes and so on. The problem is particularly acute in China, where increasing regional differences and inequality are eroding governmental poverty reduction efforts and exacerbating ecological crises. This book, based on extensive original research, examines the situation in China, especially in the Loess Plateau of Shaanxi Province. It expl.